Making and implementing public policy key concepts and issues - Catherine, Bochel (London Palgrave, 2017)
This brand new text examines power and inequalities and how these are central to our understanding of how policies are made and implemented. It introduces the concepts and theoretical approaches that underpin the study of the policy process, reflects upon key developments and applies these the practice of policy formulation and implementation
Includes index
Keywords: Social sciences; Political planning; Political planning -- Great Britain; Policy sciences; Policy sciences -- Great Britain; Policy sciences; Political planning